2014
DOI: 10.1007/s12283-014-0168-9
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of road bicycle components on vibration induced to the cyclist

Abstract: Improving comfort in road bicycle design is a paramount concern for cyclists, who are affected by the vibrations caused by constant contact with the road surface. The cycling community has deployed many efforts in the attempt to understand and improve bicycle comfort. However, these attempts have been focused on specific components such as the fork, frame and wheels without knowing their relative influence on vibration induced to the bicyclist (VIB). The objective of this paper is to assess the relative contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…This could be explained through the preponderance of the absorption by the fork. The fact is confirmed by a study [21], where it was shown that the fork and the frame were highly pertinent elements in the transmission of vibrations. The transmissibility functions resonanced frequencies range were 30-50Hz for the wrist, 16-30 Hz for the forearm, 20-90Hz for the eyeball and 10-12Hz for spine [32].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This could be explained through the preponderance of the absorption by the fork. The fact is confirmed by a study [21], where it was shown that the fork and the frame were highly pertinent elements in the transmission of vibrations. The transmissibility functions resonanced frequencies range were 30-50Hz for the wrist, 16-30 Hz for the forearm, 20-90Hz for the eyeball and 10-12Hz for spine [32].…”
Section: Discussionmentioning
confidence: 67%
“…One of the dominant factors in vibration transfer is the frame and this research is based on the frame study . Indeed [21], it has been studied by factor analysis that the influence of the components on vibration transfer in the hand-arm system is favored by the fork and tires while the whole body vibration is mainly due to the wheels and frame. Thus the frame can be studied (i) according to its geometry [22,23], or (ii) the material [24 -27].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high vertical compliance, the elastic rope did not affect the measurements. Measurements of vertical force and vertical acceleration transmitted to the different systems, i.e., the cyclist or the cyclist + gloves/bar tape, were taken using instrumented brake hoods presented by Lépine et al [11] (Figure 1-item 1). The force and acceleration signals were collected using a LMS SCADAS 24-bit acquisition system (model SCR01-08B) at a sampling frequency of 8192 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies related to the transmission of vibration by a road bicycle and road bicycle dynamic comfort have been reported in the literature. Test protocols and test rigs that mimic the road excitation in a laboratory were developed [4][5][6][7], and a wide range of transducers have been embedded within the bicycle in areas such as the brake hoods, stem, handlebars and seatpost to measure transmitted acceleration, force, power and energy to the cyclist [8][9][10][11]. The assessment of the bicycle and bicycle components' vibration transmissibility has been carried out [4,6,11], while psychophysics approaches have been used to assess cyclists' vibration perceptual thresholds, suggesting that there is a large variability among cyclists in their capacity to differentiate sensory inputs at the hands [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation